The Influence of Digital Leadership, Affective Commitment on Employee Perfomance with The Intervening Mediation of Intrinsic Motivation on Yogyakarta Appropriate Technology Development Center - Damarsasi Tunggul Pudyastowo; Kusuma Chandra Kirana; Selamet Hartanto (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
The focus of the investigation is to find out how affective commitment and digital leadership effect employee performance, with te help of intrinsic motivation. The sample collection method is quantitative by nature with the use of primary data obtained by the placement using Likert scale questionnaires. Participants in this investigation include employed who work for BPTTG Yogyakarta. The results of the study demonstrate that intrinsic motivation is seriously affected by digital leadership. Motivation is not much impacted by emotional commitment integrated. The performance of employees is significantly impacted by digital leadership. Employee output is not much impacted by affective commitment. Employee performance is not much impacted by intrinsic motivation. The affective commitment and digital leadership factors cannot be controlled by intrinsic motivation on employee performance.